Interaction and intercultural communication competence of Banten students at University of Lampung - Kartika, Tina; Ashaf, Abdul Firman; Aryanti, Nina Yudha; Wardhany, Andy Corry; Aprilia, Alfaynie Axelfa Trie (Jurnal Kajian Komunikasi, 2024)
Background: The study examines intercultural communication competence of Banten students  at the University of Lampung. In this context, the field of intercultural communication describes student participation in regular interactions in cognitive, affective, and behavioral terms. This is important because a strong understanding of intercultural communication serves as the foundation for students’ professional development at the University of Lampung. Purpose: The goals of this study are to: 1) Identify the cognitive component of intercultural communication among Banten students at the University of Lampung. 2) Identify the affective component of intercultural communication among Banten students at the University of Lampung. 3) Identify the behavioral component of intercultural communication among Banten students at the University of Lampung. 4) Develop a model of intercultural communication proficiency for Banten students at the University of Lampung. Methods: The study used informant interviews as data sources for qualitative research. The research informant included 70 students from the University of Lampung who were members of the Banten student association. The analysis process consisted of three steps: 1) Data collection, 2) Data reduction, and 3) Data presentation, which involved compiling facts used to guide decisions and actions. Results: The intercultural communication among Bantent students at the University of Lampung encompassess cognitive, affective, and behavioral aspects. Implications: Banten students at the University of Lampung can serve as an example for newcomers on how to maintain cultural distinctiveness across different regions by leveraging their cognitive, affective, and behavioral expertise in cross-cultural communication.